Mechanical performance of graded lattice structures with periodic density variations fabricated by selective laser melting - Gangxian Zhu; Fangyuan Xu; Xulei Wang; Xing Zhang; Jiaqiang Li (Materials & Design)
Functionally graded lattice structures (GLSs) represent a novel class of non-uniform structures that leverage density gradients to optimize mechanical responses based on specific functional requirements. However, current GLSs often exhibit simplistic and monotonic gradient designs, resulting in suboptimal mechanical performance. To overcome such limitation, this study proposes a set of innovative GLS featuring periodic function variations to improve mechanical behavior. Body-centered cubic GLSs with periodic density variations, including sine-wave and cosine-wave configurations, were fabricated using selective laser melting and compared against traditional uniform lattice structure and linear GLS. A comprehensive investigation of strut surface morphology, quasi-static compressive properties, and energy absorption was conducted. The findings show that GLSs designed with periodic functions exhibit a transition from layer-by-layer to segmented collapse during quasi-static compression, with deformation behavior strongly influenced by the periodic parameter. Specifically, both compressive and yield strengths increase as the period lengthens, whereas the energy absorption decreases. The optimized periodic GLS exhibits a comparable compressive strength to linear GLS but demonstrates significantly higher energy absorption efficiency, outperforming the uniform lattice structure and linear GLS by 148.10 % and 77.63 %, respectively. These results highlight the significant role of advanced density gradient designs in improving the mechanical performance of lattice structures.